Optimasi Protokol LEACH Menggunakan PSO Pada Mobile Ad-Hoc Network - Ramadhani, Afifah Dwi; Segara, Alon Jala Tirta; Wijayanto, Aditya (STMIK Budi Darma, 2022)
Mobile ad-hoc network is a wireless network with variable topology and communication routes. In a MANET network, nodes have the role of finding and handling routes to each node in the network. There are several challenges such as bandwidth, power, and direction of movement of nodes. A routing protocol is needed to determine the route and ensure that the packets sent successfully arrive at their destination to solve this problem,. In large-scale networks, the routing structure requires redundant route information, resulting in frequent overhead. We investigated the use of the LEACH protocol as a hierarchical protocol to solve the network overhead. The proposed research also adds a PSO algorithm to optimize the performance of the LEACH protocol. The research method uses simulation methods and evaluation of routing models using Network Simulator. Evaluation is prioritized on the use of traffic TCP and UDP. The results show that TCP traffic has better delay, packet loss, and PDR values compared to UDP traffic when using the LEACH protocol. When the PSO algorithm is added, the delay value in TCP traffic decreases by 47%, the packet loss value decreases by 78%, and the PDR value also increases by 0.1%.